(untitled) (Jurnal Bahasa, 2018)
This paper explores the application of theme type and language metafunction using the SFL (Systemic Functional Linguistics) theory. Data was obtained from the beginning sentences of opinion essays written by second-language students, through the identification of the themes they use. 366 sentences from 21 essays were analysed. The analysis of theme involved both marked and unmarked themes, while that of language metafunction involved three categories: ideational theme, interpersonal theme and textual theme. The analysis reveals that unmarked theme, ideational theme and textual theme are often employed by students when constructing the first sentence. This analysis may help students to develop their ideas systematically when writing, and may provide teachers with the necessary information to develop an effective method for teaching essay-writing. Keywords: composition, theme, theme type, metafunction